Leptospirosis in French Historical Medical Literature: Weil’s Disease or Kelsch’s Disease? - Tarantola, Arnaud (Am J Trop Med Hyg, 2018)
Early names for leptospirosis often indicate occupational or environmental exposure. Leptospirosis is hard to identify in the tropical setting because of co-circulating diseases. This is not the case in the temperate setting, such as Europe, where the few historical differential diagnoses were malaria, typhoid, and viral hepatitis. Leptospirosis presumably caused community epidemics in Europe before 1900 and military epidemiologists carefully documented outbreaks in “constrained settings.” Achille Kelsch (1841–1911) synthesized available military data and epidemiological perspectives to define “epidemic jaundice” as a nosological continuum, caused by an infectious agent found in muds and water. He viewed Weil’s disease as being only one form of that now well-identified disease continuum. The causative pathogen and epidemiological determinants were identified years later. The role of soils and muds as intermediate reservoirs, as suggested by Kelsch, deserves further investigation.